Dowody z Facebooka w procesie cywilnym - Bijas, Wojciech (Wydawnictwo C.H. Beck, 2017)
Nearly 10 million people – Poles – have an active account on Facebook. This means that one person in four in our country regularly leaves trace which could be used as a digital evidence. Therefore, it is not odd that in most civil proceedings the parties present evidence from Facebook. In view of huge popularity of presenting in court content from Facebook, this article is devoted to data acquired from the very social networking service. The author especially pays attention to the matter of acquiring and preserving the evidence (however, in civil proceedings these actions are taken by a party itself) and data which may be elicited from the website, and at the same time circumstances which may be proved using such data.
Keywords: digital evidence; electronic evidence; Facebook evidence; Facebook; hearing of evidence in civil lawsuit; electronic evidence searching; gathering digital evidence; gathering electronic evidence